تنفيذ تنمية القيم الدينية والأخلاق في المؤسسة روضة الأطفال ديفونيكورو ٧١ بانجارفاراكان - Umam, Nasrul; Retnaningrum, Wulandari (FONDATIA, 2023)
Finding out how the planning, execution, and assessment phases link to the instillation of moral and religious values at RA Diponegoro 71 Banjarparakan is the goal of this study. A case study style qualitative research methodology is applied. Data was gathered by means of observation, documentation, and interviewing procedures. Data condensation, data display, and conclusion drafting and verification are the three phases of data analysis employing Miles, Huberman, and Saldana. Verification of data using source triangulation. The research findings indicate that: 1) the implementation of instilling religious and moral values is carried out in curricular and co-curricular activities; 2) Religious and moral principles are implemented through co-curricular and extracurricular activities. 3. evaluation related to assessments used to determine the implementation of the cultivation of religious and moral values. Curricular activities are related to learning in the classroom in accordance with the set learning objectives, while co-curricular activities are related to daily, weekly, or annual habits. Anecdotal notes, checklist evaluations, and work products are used in assessment. Implementation challenges stem from variations in student characteristics and environmental conditions.